(untitled) (Research, Society and Development, 2020)
The rural school is conceptualized as an educational center that is far from the urban context. Multiple scientific evidences have been published and they corroborate that this institution has undergone major modifications, in recent years, its operation and internal organization having been modified. The objective of this article is to analyze which are the scientific contributions that have been published, on rural schools, in the last ten years. To this end, a search for systematized information has been carried out within two databases, establishing a procedure with four well differentiated phases: 1) Establishment of search criteria; 2) Gross selection of documents; 3) Analysis of the information and; 4) Categorization of information. The results obtained corroborate that the documents studied, there have been fifteen in total, can be classified into four categories: a) Reality of the current rural school; b) Satisfaction and teacher training; c) Digitization of rural schools and; d) Rural school as a means of local development, research and innovation. To conclude, it is essential to continue conducting research on the institution of rural schools in order to find possible barriers to learning for students from rural environments. In this way, a true educational inclusion will be developed that responds to the needs of all students.